Identifikasi Kandungan NPK dan Pengaruh Pemberian Pupuk Organik Buatan terhadap Pertumbuhan Padi Wakawondu pada Lahan Marginal - Hervina, Wa Ode; Peliyarni, Peliyarni; Ridwan, Ridwan (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
Wakawondu rice is a traditional food crop in North Buton, Southeast Sulawesi, cultivated for 400 years without chemical fertilizers. Local farmers now face soil fertility challenges due to changes in farming practices brought about by limited land availability. This study aims to analyze the nitrogen (N), phosphorus (P ₂ O₅ ), and potassium (K₂ O) content in homemade organic fertilizer and its impact on the growth of wakawondu rice in marginal lands. The organic fertilizer was prepared from a mixture of rice husks, sawdust, banana stalks, tofu residue, sugar, and EM4, incubated for 60 days. Nutrient content was measured using destruction and spectrophotometric analysis. The effectiveness of the fertilizer was tested by compa ring the growth of wakawondu rice under three conditions: homemade organic fertilizer, no fertilizer, and factory-produced compost. The results indicated that the NPK content in the homemade organic fertilizer effectively promoted plant height but had no significant effect on leaf number and width. The study concludes that homemade organic fertilizer has potential to enhance rice growth on marginal lands, though its effect on leaf parameters remains limited. Further research is recommended to optimize ferti lizer formulation and understand other factors impacting crop productivity.